Pengaruh Metode SQ4R Terhadap Keterampilan Membaca Pemahaman Siswa Kelas IX MTsN 4 Pesisir Selatan - Nadya Fadhila Rahmi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to determine whether there is an effect before using the SQ4R method on reading comprehension skills of class IX students of MTsN 4 Pesisir Selatan and after using the SQ4R method on reading comprehension skills of grade IX students of MTsN 4 Pesisir Selatan. This research is an experimental research with a research design used One Group Pretest-Posttest Design. The population in this study were students of class IX MTsN 4 Pesisir Selatan. The sample was taken by using purposive sampling technique. The data of this study were the scores from the reading comprehension skills of class IX students of MTsN 4 Pesisir Selatan before and after using the SQ4R method. Data were analyzed by t-test. The results of this study show that there is an effect before and after using the SQ4R method on reading comprehension skills of class IX students of MTsN 4 Pesisir Selatan, namely tvalue> ttable (4.85> 1.67). The average reading comprehension skills of class IX MTsN 4 Pesisir Selatan students after using the SQ4R method was higher than before using the SQ4R method (92.31> 48.72). Thus it can be concluded that the SQ4R method has a significant effect on reading comprehension skills of class IX students of MTsN 4 Pesisir Selatan.